Adoption and everyday use of artificial intelligence by NHS knowledge and library professionals in England : Part I: context and support (Journal of EAHIL, 2024)
Knowledge and library professionals in the UK are exploring the use of generative artificial intelligence (AIand contributing to discussions concerning data and knowledge, in the context of a country keen to drivethe adoption of data driven services and digital technologies. In this article we introduce the driversadoption of AI within NHS Knowledge and Library Services (KLS) in England, and the methodologies employedto upskill staff in new technologies. This is set against the backdrop of the ethics and risks associated withwhich provide opportunities for KLS to improve services and support the safe and effective adoption of AIfollow up article we provide practical use case studies, to help inspire experimentation and adoption.